2020
DOI: 10.1002/aur.2332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating heterogeneity in ASD symptomatology, cognitive ability, and adaptive functioning among 16p11.2 CNV carriers

Abstract: Individuals with 16p11.2 copy number variant (CNV) show considerable phenotypic heterogeneity. Although autism spectrum disorder (ASD) is reported in approximately 20–23% of individuals with 16p11.2 CNVs, ASD‐associated symptoms are observed in those without a clinical ASD diagnosis. Previous work has shown that genetic variation and prenatal and perinatal birth complications influence ASD risk and symptom severity. This study examined the impact of genetic and environmental risk factors on phenotypic heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 62 publications
2
30
3
Order By: Relevance
“…Sex differences in 16p11.2 CNVs-Several neurodevelopmental disorders display a sex bias where males are at a higher risk [56]. In agreement with this, the ratio of males to females with either ASD or ID shows a male predominance in both 16p11.2 CNVs [57], suggesting that being female is a protective factor when predicting overall ASD severity in either 16p11.2 CNV [58]. However, another study found that sex was not a significant predictor of psychosis in 16p11.2 CNV carriers [44].…”
Section: Neurodevelopmental Phenotypes Associated With 16p112 Cnvsmentioning
confidence: 57%
“…Sex differences in 16p11.2 CNVs-Several neurodevelopmental disorders display a sex bias where males are at a higher risk [56]. In agreement with this, the ratio of males to females with either ASD or ID shows a male predominance in both 16p11.2 CNVs [57], suggesting that being female is a protective factor when predicting overall ASD severity in either 16p11.2 CNV [58]. However, another study found that sex was not a significant predictor of psychosis in 16p11.2 CNV carriers [44].…”
Section: Neurodevelopmental Phenotypes Associated With 16p112 Cnvsmentioning
confidence: 57%
“…The general lack of phenotypes in our and their coisogenic mouse models of 16p11.2 deletion could be interpreted as suggesting that developmental neuropsychiatric disorders seen at elevated rates among 16p11.2 deletion carriers are not primarily caused by this chromosomal deletion alone. This CNV might require other coexisting genetic variants, including second CNVs [ 44 ] and common genetic variation [ 21 , 45 ], and environmental insults, such as preterm and C-section birth [ 46 ] to be fully symptomatic. Alternatively, this CNV might manifest its impacts on subdimensions that are predominantly used for certain functions in a given species.…”
Section: Discussionmentioning
confidence: 99%
“…CNVs in 16p11.2 are among the most frequently identified pathogenic genetic changes in autism spectrum and other neurodevelopmental disorders [5,6]. They exemplify the variable expressivity and pleiotropy that tends to be the norm for high-risk genetic variants: deletions of this genomic interval are strongly associated with autism and intellectual disability [7], while duplications appear to increase risk more strongly towards psychotic disorders [8].…”
Section: Actionable Genomics In Psychiatry: Example Of a 16p112 Dupli...mentioning
confidence: 99%